2011
DOI: 10.1098/rsta.2011.0041
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations of the behaviour of a drop in a square pipe flow using the two-phase lattice Boltzmann method

Abstract: The lattice Boltzmann method for multi-component immiscible fluids is applied to simulations of the behaviour of a drop in a square pipe flow for various Reynolds numbers of 10 < Re < 500, Weber numbers of 0 < We < 250 and viscosity ratios of h = 1/5, 1, 2 and 5. It is found that, for low Weber numbers, the drop moves straight along a stable position on the diagonal line of the pipe section, and it moves along the centre axis of the pipe for larger Weber numbers. We obtain the boundary of the two different beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Most importantly, small particles at high Reynolds numbers have their stable equilibrium positions on the main axes, while larger particles at lower Reynolds number move to the equilibrium positions on the diagonals. This is a new result compared to previous treatments 6,8,9 .…”
Section: Square Channelsmentioning
confidence: 57%
See 3 more Smart Citations
“…Most importantly, small particles at high Reynolds numbers have their stable equilibrium positions on the main axes, while larger particles at lower Reynolds number move to the equilibrium positions on the diagonals. This is a new result compared to previous treatments 6,8,9 .…”
Section: Square Channelsmentioning
confidence: 57%
“…In square channels they are typically found halfway between the channel center and the centers of the channel walls 7 . In numerical studies also migration to positions on the diagonals are observed 8,9 . In rectangular channels the number of equilibrium positions is further reduced to…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…The LKS, initially developed as a way to reduce memory consumption in LBM 67 , is a modified version of the SRT collision operator which allows for an additional relaxation coefficient (called second relaxation coefficient throughout this manuscript) for higher-order kinetic moments. This approach has mostly been applied to cases involving large variations in the diffusion coefficient (viscosity for flow solvers), such as non-Newtonian flows [68][69][70] , multi-phase flows [71][72][73][74] , thermal flows 75 and viscous fingering in porous media 76,77 . In all these examples the viscosity (or species and thermal diffusion coefficient) spans a rather large interval of values.…”
Section: Introductionmentioning
confidence: 99%